Functional characterization of a BRAF insertion mutant associated with pilocytic astrocytoma - Eisenhardt, Anja; Olbrich, Heike; Röring, Michael; Janzarik, Wibke; Anh, Ton Nu Van; Cin, Huriye; Remke, Marc; Witt, Hendrik; Korshunov, Andrey; Pfister, Stefan; Omran, Heymut; Brummer, Tilman (International journal of cancer, 2011)
Pilocytic astrocytoma (PA) is emerging as a tumor entity with dysregulated Ras/Raf/MEK/ERK signaling. Common genetic lesions observed in PA, which are linked to aberrant ERK pathway activity, include either NF1 inactivation, KRAS or BRAF gain-of-function mutations. To investigate the mutation spectrum within the proto-oncogene encoding the Ser/Thr-kinase B-Raf in more detail, we analyzed 64 primary tumor samples from children with PA including two patients with neurofibromatosis type 1 (NF1). The well-known BRAFV600E mutation was found in 6/64 (9.38%) of our samples. For the first time, we report concomitant presence of a somatic BRAFV600E mutation in an NF1 patient indicating that more than one Ras/ERK pathway component can be affected in PA. Furthermore, 2/64 (3.13%) of our samples carried a 3-bp insertion in BRAF resulting in the duplication of threonine 599. This conserved residue is located within the activation segment and, if phosphorylated in a Ras-dependent manner, plays a key role in Raf activation. Here, we demonstrate that this mutant (B-RafinsT) and another B-Raf mutant, which carries two additional threonine residues at this position, display an in vitro kinase activity and cellular MEK/ERK activation potential comparable to those of B-RafV600E. Notably, replacement of threonines by valine residues had similar effects on B-Raf activity, suggesting that the distortion of the peptide backbone by additional amino acids rather than the insertion of additional, potential phosphorylation sites destabilizes the inactive conformation of the kinase domain. We also demonstrate that B-RafinsT and B-RafV600E, but not B-Rafwt, provoke drastic morphological alterations in human astrocytes.